2011
DOI: 10.1097/mpg.0b013e3182093b32
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metabolic Control on Bone Quality in Phenylketonuria and Mild Hyperphenylalaninemia

Abstract: Good compliance with treatment in PKU during adolescence and adulthood is desirable because diet discontinuation is associated with bone loss. Mild HPA seems not to be complicated by bone damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
1
13
0
1
Order By: Relevance
“…This suboptimal bone profile does not necessarily lead to increased fracture rate; however, data on this field are contradictory (18). On the other hand, patients with mHPA had normal growth as reported previously (16) and their MM and FM were not different from the reference population; however, LS BMD was decreased in comparison to controls. To our knowledge, there was no other study concerning BMD assessment of patients with mHPA by DXA.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This suboptimal bone profile does not necessarily lead to increased fracture rate; however, data on this field are contradictory (18). On the other hand, patients with mHPA had normal growth as reported previously (16) and their MM and FM were not different from the reference population; however, LS BMD was decreased in comparison to controls. To our knowledge, there was no other study concerning BMD assessment of patients with mHPA by DXA.…”
Section: Discussionsupporting
confidence: 78%
“…It is well established that bone health in PKU is at risk of morbidities. Numerous studies have shown low BMD in patients with PKU, which is attributed to different predisposing factors including low protein as well as fatty acid intake (14, 15) and the disorder itself through a direct toxic effect of excessive Phe on bones (16). Our patients had lower TB BMD than controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A csökkent csontsűrűség mellé fogászati rendellenességek és kiegyensúlyozatlan csontnövekedés is társulhat [5]. A tö-rési kockázatot mindössze egyetlen kutatás vizsgálta, mely 2,6-szeres kockázatnövekedést talált az egészséges kontrollcsoporthoz képest [6].…”
unclassified